MASALAH EKONOMI SEBAGAI TANTANGAN KELUARGA KRISTIANI ZAMAN INI - Ade Theresia Permata Sari Br Marmata; Aji Sukma Dewa; Jiang Qing; Vu Duc Quang; Herwindo Chandra (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2026)
This study departs from the premise that the Christian family as ecclesia domestica is confronted with structural and multidimensional economic pressures. Low financial literacy, the expansion of consumerist culture, technological unemployment, customary demands, and currents of secularization generate vulnerabilities that affect sacramental stability, relational cohesion, and the continuity of children’s faith formation. The research aims to identify the determining factors of family economic crisis, to evaluate its pastoral–theological consequences, and to formulate ecclesial responses within the horizon of Catholic Social Teaching. The study employs a qualitative approach through library research by analytically integrating magisterial documents and empirical findings. The results reveal the emergence of an economic vulnerability trap, manifested in increasing marital conflict, long-term labor migration, declining liturgical participation, and the weakening of intergenerational faith transmission. Conversely, Eucharistic spirituality, collaborative financial governance, and empowerment-oriented diakonia correlate with greater family resilience and renewed ecclesial engagement. Therefore, strengthening faith-based financial literacy and integrative family accompaniment becomes an urgent pastoral priority.